THE ROLE OF WHISTLEBLOWING, CULTURE, AND ORGANIZATIONAL COMMITMENT IN FRAUD PREVENTION - Yuhanis Ladewi; Muhammad Fahmi; Fauziah, Alfina Damayanti; Zuraidah, Ida (UPT Publikasi Ilmiah UNISBA, 2024)
This study aims to find out and analyze the role of whistleblowing culture, and organizational commitment in fraud prevention. The types of research used are descriptive and associative. The population used is 11 branch stores with a saturated sample of 85 respondents. This study uses primary and secondary data. The data collection methods are interviews, questionnaires, and documentation. To test the data, this research applies validity and reliability tests. The data analysis techniques used are descriptive statistics and inferential statistical analysis, namely classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test) and multiple linear regression analysis, determination coefficient, and t-test. This study uses the analysis technique of the SPSS Version 25 data processing program. Based on the results processed, 85 respondents are all valid and reliable. The results of this study can be concluded partially (t-test) showing that whistleblowing, organizational culture, and organizational commitment have a significant effect on fraud prevention at PT Sumber Alfaria Trijaya Tbk in Plaju District. Keywords : Cheating Prevention, Organizational Commitment, Organizational Culture, Whistleblowing